2019
DOI: 10.3171/2019.5.peds19200
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative acute neurological deficits in instrumented pediatric cervical spine fusions

Abstract: OBJECTIVEPediatric cervical deformity is a complex disorder often associated with neurological deterioration requiring cervical spine fusion. However, limited literature exists on new perioperative neurological deficits in children. This study describes new perioperative neurological deficits in pediatric cervical spine instrumentation and fusion.METHODSA single-center review of pediatric cervical spine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A multicenter study investigating the long-term effects of rigid instrumentation and surgical fusion found that 95% of patients had complete or significant resolution of neurologic symptoms following instrumentation, with 66% of patients demonstrating continued vertical growth of the subaxial spine [ 11 ]. Likewise, a retrospective review of 184 anterior- and posterior-approach cervical spine instrumentation and fusion found that 96.7% of children improved or stabilized neurologic outcome following traumatic injury [ 14 ]. Anterior cervical approaches have been less commonly studied but are also promising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study investigating the long-term effects of rigid instrumentation and surgical fusion found that 95% of patients had complete or significant resolution of neurologic symptoms following instrumentation, with 66% of patients demonstrating continued vertical growth of the subaxial spine [ 11 ]. Likewise, a retrospective review of 184 anterior- and posterior-approach cervical spine instrumentation and fusion found that 96.7% of children improved or stabilized neurologic outcome following traumatic injury [ 14 ]. Anterior cervical approaches have been less commonly studied but are also promising.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches have proven to be successful in pediatric cervical injury cases. They have been used in cases of spinal fracture-dislocations, burst fractures, compression fractures with concomitant deformity, and atlanto-occipital dislocation (Table 1) [1,[6][7][8][9][10][11][12][13][14][15]. The most common surgical intervention approach is posterior cervical fusion and occipitocervical fusion using autograft or allograft (94% vs. 80% fusion rate) has an overall fusion rate of 93% based on a systemic literature review [16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited space and intimate anatomic relationship, posterior cervical spine surgery inherently puts neural structures at risk. Reported incidence of neurological complications associated with these procedures in the paediatric population is variable (0, 0.3%, 3.3%) 3–5…”
Section: Discussionmentioning
confidence: 99%
“…As it is known, a recovery of neurological disturbances and consequently of functional restriction can take a long time [11]. The neurological status on the day of discharge from acute care hospital mostly is not a nal result and can be signi cantly improved due to medical rehabilitation [25]. Therefore we decided to establish a su x "r" for de ning the long-term outcome.…”
Section: Classi Cation Of Postoperative Neurological Complications (Cmentioning
confidence: 99%
“…Obviously, the fact that improvement of neurological disturbances can take a long time [11,25] and the neurological state at the time of discharge from acute care hospital mostly is not a nal result, leads to the requirement of evaluation of neurological state after completed rehabilitation. For this purpose, the suggested su x "r" appears to be useful for observation of neurological complications in the follow-up period and determination of the nal outcome.…”
Section: A Classi Cation Concentrating Only On Daily Life Activities mentioning
confidence: 99%